The correct answer for the question that is being presented above is this one: "2(x - 1)(3x + 4) = 0."
<span>6x 2 + 2x - 8 = 0
(2x - 2) (3x + 4) = 0
2(x - 1)(3x + 4) = 0
The correct answer for the question that is being presented above is this one: "</span><span>(x - 4)^2 = -19."</span><span>
x2 - 8x + 3 =0
x2 - 8x + 16 = -3 - 16
(x - 4)(x - 4) = -19
(x - 4)^2 = -19</span>
Answer:
1/6^8
Step-by-step explanation:
the answer is the one right next to the submit answer
Step-by-step explanation:
<em>1st year</em>:
(1200 x 3.5 x 1) ÷ 100 = $42
<em>2nd year:</em>
(1242 x 3.5 x 1) ÷ 100= $43.47
<em>3rd year:</em>
(1285.47 x 3.5 x 1) ÷ 100= $44.99≈ $45
<em>4th year:</em>
(1330.47 x 3.5 x 1) ÷ 100= $46.56
Compound interest:
$(42 + 43.47 + 45 + 46.56)
=<u>$ 177.03</u>
<span>Cube root of 0.000064 = 0.04
hope it helps
------------------</span>
8+11=19. So there’s 19 roses in total